1998
DOI: 10.1128/mcb.18.11.6745
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of Mouse RIP140, a Corepressor for Nuclear Orphan Receptor TR2

Abstract: The mouse homologue of the human receptor-interacting protein 140 (RIP140) was isolated from a mouse embryonic cDNA library in yeast two-hybrid screening experiments by using the ligand binding domain (LBD) of nuclear orphan receptor TR2 as the bait. The receptor-interacting domains of mouse RIP140 were mapped to the regions containing the LXXLL motif (where L is leucine and X is any amino acid), and the RIP140-interacting domain of TR2 was mapped to its C-terminal 10-to 20-amino-acid sequence, a putative acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
142
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(154 citation statements)
references
References 47 publications
9
142
0
3
Order By: Relevance
“…Several bifunctional coregulators of NR have been reported to exist, including ZAC1, NSD1, and RIP140, which tend to behave either as coactivators or as corepressors under distinct circumstances (17)(18)(19)(20). Although the switching mechanisms responsible for the bifunctionality of these coregulators have yet to be elucidated, mouse variant ZAC1 (mZac1b), which binds to many other coregulators including GRIP1, CBP, and p300, has FIG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several bifunctional coregulators of NR have been reported to exist, including ZAC1, NSD1, and RIP140, which tend to behave either as coactivators or as corepressors under distinct circumstances (17)(18)(19)(20). Although the switching mechanisms responsible for the bifunctionality of these coregulators have yet to be elucidated, mouse variant ZAC1 (mZac1b), which binds to many other coregulators including GRIP1, CBP, and p300, has FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Some transcriptional coregulators for NR-mediated transcription, such as ZAC1, NSD1, and RIP14, have been demonstrated to possess dual functions, acting as both coactivators and corepressors (17)(18)(19)(20). Recently, the nuclear protein PELP1 (proline-, glutamic acid-, and leucine-rich protein 1) has been proposed to be another dual-function coregulator for NR-mediated transcription; i.e.…”
mentioning
confidence: 99%
“…COS-1 cells were used in co-transfection experiments to determine the effects of added nuclear receptors on the reporter gene activity as well as mammalian two-hybrid interaction experiments as described (16,20). All the COS-1 cultures were maintained in Dulbecco's modified Eagle's medium containing dextran charcoal-treated serum (DCC medium).…”
Section: Construction Of Reporters and Expression Vectors-mentioning
confidence: 99%
“…In addition, a novel receptor heterodimeric pathway was identified that involved heterodimers of TR2 and TR4 (19). Recently, the mouse nuclear receptor-interacting protein 140 (RIP140) was cloned and demonstrated as a co-repressor for TR2 by interacting with its LBD (20).…”
mentioning
confidence: 99%
“…The coregulator RIP140 contains 10 LXXLL motifs and like a classic coactivator interacts preferentially with ligand-bound nuclear receptors (11). However, RIP140 inhibits the transactivation function of ligand-bound nuclear receptors in reporter assays (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). RIP140 is now recognized as one of the first proteins of a unique class of coregulators that are able to repress ligand-bound nuclear receptors (23).…”
mentioning
confidence: 99%